Innovation in Science Learning through the Integration of the Discovery Learning Model Assisted by Student Worksheets in Elementary School Learning: Inovasi Pembelajaran IPAS melalui Integrasi Model Discovery Learning Berbantuan LKPD pada Pembelajaran Sekolah Dasar - Amris; Estuhono; Raimon Efendi (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
This study aims to improve students’ learning outcomes in IPAS through the implementation of the Discovery Learning model assisted by student worksheets (LKPD) in the fourth grade of SDN 66/II Simp. Rantau Ikil. The problem addressed in this study is the low learning outcomes, as indicated by low average scores and low learning mastery levels. This research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were 23 fourth-grade students. The results showed a significant improvement in learning outcomes. The average score increased from 25.25 in the pre-cycle to 66.20 in Cycle I and further improved to 76.30 in Cycle II. The percentage of learning mastery also increased from 35% in the pre-cycle to 57% in Cycle I and reached 87% in Cycle II. In addition, teacher activity improved from a score of 72 to 76, while student activity increased from 30 to 40. The novelty of this study lies in the integration of the Discovery Learning model with activity-based LKPD designed as instructional scaffolding to support students’ independent concept discovery. The findings indicate that the implementation of the Discovery Learning model assisted by LKPD is effective in improving students’ learning outcomes and enhancing the quality of the learning process.